2017
DOI: 10.1590/2359-3997000000201
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between adipokines and carotid intima media thickness in a group of obese Romanian children: is small for gestational age status an independent factor for cardiovascular risk?

Abstract: Objective: To investigate the relationship between markers of adiposity and common carotid artery (CIMT) in obese children born small for gestational age (SGA) versus appropriate for gestational age (AGA), to establish cut-off values for CIMT in obese pediatric populations. Subjects and methods: A cross-sectional study was carried out over a 1-year period (Jul 2013 -June 2014). We analyzed 122 obese patients aged 4-20 (mean age 14.9 ± 2.28). Twenty-six patients were born SGA. CIMT was measured in all the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…CIMT is a marker to assess preclinical atherosclerosis and is associated with future cardiovascular events (van den Oord et al 2013). Increased CIMT is inversely related to adipokine levels and HDL-cholesterol (Gilardini et al 2011;Stroescu et al 2017). Goeller et al recently showed that EAT volume was inversely related to adipokines, HDL-cholesterol and angiotensin in adults (Goeller et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…CIMT is a marker to assess preclinical atherosclerosis and is associated with future cardiovascular events (van den Oord et al 2013). Increased CIMT is inversely related to adipokine levels and HDL-cholesterol (Gilardini et al 2011;Stroescu et al 2017). Goeller et al recently showed that EAT volume was inversely related to adipokines, HDL-cholesterol and angiotensin in adults (Goeller et al 2018).…”
Section: Discussionmentioning
confidence: 99%